THE ADVANTAGES OF SCAN-TO-BIM IN DOCUMENTING CULTURAL HERITAGE ASSETS IN MALAYSIA - Md. Sharif, Harlina; Hazumi, Hazman; Hishamuddin, Iman Asilah (2019)
Cultural heritage conservation is a complex process requiring innovative methods and techniques to facilitate its restoration, management and valorization. Accurate documentation of heritage assets is crucial in ensuring that any changes, repair, addition or demolition of parts of the assets are properly recorded to maintain the authenticity of the assets. The aim of this study is to establish the advantages of scan-to-BIM application in documenting cultural heritage assets in Malaysia as a critical procedure in the steps to conserve the asset. The methodology adopted in this study is mixed mode. Primary data is acquired from the use of Faro 3D laser scanner (3DTLS) at reconnaissance stage on Gedung Raja Abdullah, Klang. This study analyses the Scan-to-BIM advantages in order to ascertain the best practice method in documenting historical buildings and managing cultural heritage assets. The output from this study demonstrates the versatility of data collected through Scan-to-BIM that allows them to be manipulated into different forms, which subsequently can be used for various purposes.